BO‘LAJAK PEDAGOGLARNING O‘ZIGA ISHONCHINI RIVOJLANTIRISH BO‘YICHA QIYOSIY NATIJALAR TAHLILI - Dawkeeva, A. (SCIENCE and SOCIETY, 2024)
This article provides scientific and theoretical information about the analysis of comparative results in the factors of "self-confidence", "trust in others", "emotional stability" and "cognitiveness" in the development of self-confidence.